2005
DOI: 10.1002/cncr.21633
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of phenoxodiol‐induced apoptosis in ovarian carcinoma cells

Abstract: BACKGROUND Previously, it was demonstrated that phenoxodiol induces apoptosis in epithelial ovarian carcinoma (EOC) cells and that it is capable of sensitizing these cells to Fas‐mediated apoptosis. The objectives of this study were to determine whether phenoxodiol can also act as chemosensitizer to chemotherapeutic agents and to characterize the molecular mechanism behind its sensitizing effect. METHODS Ten EOC cell lines were used in this study. The effect of phenoxodiol on the inhibitory concentration 50% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 14 publications
5
96
0
Order By: Relevance
“…These studies have shown that in some cancers phenoxodiol appears to be strong enough to work on its own as a monotherapy. However, one of the major benefits of phenoxodiol is its ability to sensitize cancer cells to the antitumor effects of conventional chemotherapeutics [137]. It has been found that cancer cells that have become resistant to the effects of conventional chemo-therapeutics, phenoxodiol could restore chemosensitivity [138].…”
Section: Genistein Analogues and Related Studiesmentioning
confidence: 99%
“…These studies have shown that in some cancers phenoxodiol appears to be strong enough to work on its own as a monotherapy. However, one of the major benefits of phenoxodiol is its ability to sensitize cancer cells to the antitumor effects of conventional chemotherapeutics [137]. It has been found that cancer cells that have become resistant to the effects of conventional chemo-therapeutics, phenoxodiol could restore chemosensitivity [138].…”
Section: Genistein Analogues and Related Studiesmentioning
confidence: 99%
“…Cells (2×10 5 ) were activated by adding 10 µg/mL anti-CD3 and 5 µg/mL anti-CD28 and 20 U/mL interleukin-2 per well. Cells were incubated at 37°C in 5% CO2 in a humidified incubator for 4 to 5 days until large numbers of large spherical aggregates or bursts of lymphocytes were observed.…”
Section: In Vitro Activation Of T Cellsmentioning
confidence: 99%
“…1,2 Phenoxodiol has been referred to as a pan-cancer drug, 3 causing apoptosis in cancer cell lines and murine cancer models via both intrinsic and extrinsic pathways. [4][5][6][7][8][9][10][11][12][13][14] Plasma membrane electron transport (PMET) has been shown to be a target of phenoxodiol in several studies with cancer cell lines. 3,13,15 PMET consists of an outer membrane (surface) NADH-oxidoreductase, redox-recycling plasma membrane ubiquinone and an inner membrane NADH-oxidoreductase.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified the core molecular structure required for benzopyran compounds to exert these functions and using this pharmacophore, we have created firstand second-generation drugs that exhibit significant activity against several types of cancer, including ovarian, both in vitro and in vivo. Phenoxodiol and triphendiol are first-generation compounds that have been shown to induce caspase-mediated cell death (20)(21)(22)(23)(24)(25). In ovarian cancer, phenoxodiol acts as a chemosensitizer and thus lowers the IC 50 for standard-of-care chemotherapy agents (20-22, 26, 27).…”
Section: Introductionmentioning
confidence: 99%